In Physics Education, Perception Matters. Issue 3 (September 2015) - Sattizahn, Jason R.; Lyons, Daniel J.; Kontra, Carly; Fischer, Susan M.; Beilock, Sian L.
ABSTRACT Student difficulties in science learning are frequently attributed to misconceptions about scientific concepts. We argue that domain‐general perceptual processes may also influence students' ability to learn and demonstrate mastery of difficult science concepts. Using the concept of center of gravity (CoG), we show how student difficulty in applying CoG to an object such as a baseball bat can be accounted for, at least in part, by general principles of perception (i.e., not exclusively physics‐based) that make perceiving the CoG of some objects more difficult than others. In particular, it is perceptually difficult to locate the CoG of objects with asymmetric‐extended properties. The basic perceptual features of objects must be taken into account when assessing students' classroom performance and developing effective science, technology, engineering, and mathematics (STEM) teaching methods.